2015
DOI: 10.1039/c4tb01967a
|View full text |Cite
|
Sign up to set email alerts
|

Design of multi-functional linear polymers that capture and neutralize a toxic peptide: a comparison with cross-linked nanoparticles

Abstract: In this paper, a library of multi-functional linear poly-N-isopropylacrylamide (pNIPAm) polymers having a range of molecular weights and functional groups were synthesized and their interaction with the hemolytic peptide, melittin, was examined. The linear pNIPAm (LPs) containing both tert-butyl group and carboxylic acids bound with the peptide by a combination of hydrophobic and electrostatic interactions and neutralized its toxicity. The melittin binding capacity and affinity of each LP was quantified and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…10,14 It has been reported that PLs with larger molecular weight shows stronger affinity to melittin than the smaller one, because the larger PLs has a higher degree of freedom in its structure and more easily map onto melittin to form high affinity binding sites. 10,14 It has been reported that PLs with larger molecular weight shows stronger affinity to melittin than the smaller one, because the larger PLs has a higher degree of freedom in its structure and more easily map onto melittin to form high affinity binding sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,14 It has been reported that PLs with larger molecular weight shows stronger affinity to melittin than the smaller one, because the larger PLs has a higher degree of freedom in its structure and more easily map onto melittin to form high affinity binding sites. 10,14 It has been reported that PLs with larger molecular weight shows stronger affinity to melittin than the smaller one, because the larger PLs has a higher degree of freedom in its structure and more easily map onto melittin to form high affinity binding sites.…”
mentioning
confidence: 99%
“…Nevertheless, 30-mer PL binds melittin strongly because of specific features in the peptide sequence, including the motif KRKR instead of KKKK, as in ponericin: Presumably, the two guanidium ions on the KRKR sequence enabled selective affinity to melittin due to strong electrostatic interaction between guanidium cation and carboxylate anion supported by two parallel hydrogen bonds. The ability of PLs to neutralize melittin toxicity was investigated by hemolysis neutralization assay (S5) 7,14 . 6 To confirm the interaction between peptide and PLs, we used isothermal titration calorimetry (ITC).…”
mentioning
confidence: 99%
“…Additionally, typically, PPIs are larger than 1000 Å 2 and involve more than 20 amino acid contacts. 3,4) Synthetic polymers, such as dendrimers, 5) linear polymers, [6][7][8] and polymer nanoparticles (NPs), 9,10) have the potential to work as protein affinity reagents by mimicking protein-protein interactions 11) (Fig. 1b).…”
Section: Protein Affinity Reagentsmentioning
confidence: 99%
“…Recent studies on interactions between biomolecules and synthetic polymers reveal that polymeric nanoparticles or linear copolymers with special functions and components could exhibit high binding property and even selectivity to biomolecules like peptides, proteins and carbohydrates [40][41][42][43][44][45][46][47]. Schrader and co-work-ers first attempted to synthesize a library of random statistical linear copolymers for the discovery of protein affinity [40].…”
Section: Affinity Screening Strategymentioning
confidence: 99%